2014
DOI: 10.1038/ncomms5861
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-stabilized lithium caesides with caesium anions beyond the −1 state

Abstract: Main group elements usually assume a typical oxidation state while forming compounds with other species. Group I elements are usually in the þ 1 state in inorganic materials. Our recent work reveals that pressure may make the inner shell 5p electrons of Cs reactive, causing Cs to expand beyond the þ 1 oxidation state. Here we predict that pressure can cause large electron transfer from light alkali metals such as Li to Cs, causing Cs to become anionic with a formal charge much beyond À 1. Although Li and Cs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 56 publications
3
57
1
Order By: Relevance
“…This structure is an interesting example of Li-N compounds which can be viewed as a combination of a single Li atom and a slightly distorted Li 12 N icosahedral group (with N atom inside the Li 12 icosahedron). A similar Li 12 Cs icosahedron is present in the Pnna structure of Li 3 Cs compound 29 , where neighboring icosahedra share Li-Li edges. However, the Li 12 N icosahedra are isolated and do not share Li atoms with each other in our Li 13 N compound.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This structure is an interesting example of Li-N compounds which can be viewed as a combination of a single Li atom and a slightly distorted Li 12 N icosahedral group (with N atom inside the Li 12 icosahedron). A similar Li 12 Cs icosahedron is present in the Pnna structure of Li 3 Cs compound 29 , where neighboring icosahedra share Li-Li edges. However, the Li 12 N icosahedra are isolated and do not share Li atoms with each other in our Li 13 N compound.…”
Section: Resultsmentioning
confidence: 83%
“…The Li-N bond lengths in the Li 12 N icosahedron are 1.934, 1.951 and 2.011 Å, i.e. nearly identical, and Li-Li distances are also nearly identical, ranging from 2.026 to 2.113 Å (maximum difference 4.3%, to compare with 22.3% in Li 3 Cs 29 ).…”
Section: Resultsmentioning
confidence: 91%
“…The most significant conclusion following from this first part of our experimental study is that the formation of Li-Cs crystalline alloys does occur unambiguously in a pressure regime much lower than theoretically predicted, that is, >50 GPa ( 3 ). The observed structures are likely not related to the predicted Li-rich Cs alloys ( 4 ).…”
Section: Resultsmentioning
confidence: 86%
“…Zhang and Zenger predicted that intermetallic crystalline structures can be stabilized as a result of a pressure-induced increase in charge transfer from Li to Cs. A more recent study also predicted that under pressure, electrons can be transferred from Li in Li-rich Li-Cs alloys, causing Cs to become anionic with a formal charge larger than −1 ( 4 ). These proposals are not unreasonable because pressure-promoted electron transfer in solids is not uncommon.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequent experimental study by in situ synchrotron powder x-ray diffraction [22] demonstrated that the Li-Cs alloy could be synthesized at very low pressure (>0.1 GPa), and analysis of the valence charge density also showed that electrons are donated from Cs to Li, resulting in a charge state of -1 for Li. Interestingly, Cs can also obtain electrons from Li and become anionic with a formal charge much beyond -1 at high pressures, as Botana et al [23] reported in the stable LinCs (n=2-5) compounds under pressures above 100 GPa using first principles method within DFT scheme. This phenomenon can partially explained by tracking the variation of electronegativity between Li and Cs with pressure [24] .…”
Section: Introductionmentioning
confidence: 83%